Semiconductor Lasers and Laser Dynamics IX 2020
DOI: 10.1117/12.2557305
|View full text |Cite
|
Sign up to set email alerts
|

Control of dual-wavelength laser using monolithically integrated phase-controlled optical feedback

Abstract: In this conference proceeding, we present a novel technique to control the emission of dual-wavelength lasers. Using a well designed external cavity, we demonstrate that tuning the optical feedback phase allows to efficiently tailor the output power balance between the two wavelengths emitted by the laser. With this technique, a complete switch between one and the other mode can also be achieved and we report a suppression ratio up to 40 dB. Due to its simplicity, the structure can be monolithically integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Using phase-controlled optical feedback we show that the balance in power between the two wavelengths can be tuned with only one parameter, the EOPM voltage. We have shown that it is possible to switch between the wavelength with a high suppression ratio of up to 25 dB and beyond [11] . In addition, this approach appears to provide switching capability at a fast pace in the nanosecond range, and possibly faster.…”
Section: Discussionmentioning
confidence: 96%
“…Using phase-controlled optical feedback we show that the balance in power between the two wavelengths can be tuned with only one parameter, the EOPM voltage. We have shown that it is possible to switch between the wavelength with a high suppression ratio of up to 25 dB and beyond [11] . In addition, this approach appears to provide switching capability at a fast pace in the nanosecond range, and possibly faster.…”
Section: Discussionmentioning
confidence: 96%
“…The slave laser is a dual-cavity InP distributed Bragg reflector (DBR) laser with a single semiconductor optical amplifier (SOA) serving as the common gain medium. The dual cavity laser is established through the sequential arrangement of two DBR structures on one side, and a two-port broadband reflector (BR) on the other side [32,33]. The pitch of the DBRs is set to obtain a spectral separation of 10 nm between the two reflectivity bands.…”
Section: Experimental Setup For the Injection Of Ssb Signalmentioning
confidence: 99%
“…Such a functionality is promising for various applications in the context of THz signal generation, THz communication systems or conversion of signal wavelengths using optical injection, especially if the wavelength switching process is fast. Wavelength switching occurs when one wavelength undergoes constructive interference in the external feedback cavity while the other suffers from destructive interference [1]. By shifting the phase in the feedback cavity, with e.g.…”
Section: Introductionmentioning
confidence: 99%